Meningkatkan Keterampilan Berbicara Siswa SMK menggunakan Role Play dan Klip Video - Ambarsari, Lies; Noor, Muhamad Arief (Neolectura, 2024)
The objectives of this research were to describe, Improving Vocational School Student’s Speaking Skill Using Role Play and Video Clips. The subjects of this research were the ten grade of students SMK Nusantara Ciputat in the academic year of 2017/2018. The number of the subjects were 31 students. This research was classroom action research. The process of this research was conducted in three cycles. The data was collected by using observation checklist to know the events in the classroom during teaching-learning process. Besides, she also used the test to get the students? scores to know the improvement of students? skill in speaking from their score. The data were analyzed by using qualitative analysis. The result of the research shows that Improving Vocational School Student’s Speaking Skill Using Role Play and Video Clips SMK Nusantara Ciputat in the academic year of 2017/2018 could improve students speaking skill. This successfulness could be seen from the result of students’ average score and good responses by students. The result of getting all of the treatment Speaking Skill Using Role Play average score increased in line with the increase of the students' achievement in each cycle. Before getting the treatment students' average score was 63,64 and after giving treatment was 69,84, so it increased 6.4. The average score of students in the first cycle was 63,09, the second cycle was 65,96, and the third cycle was 67,35. Based on the result of the research, it can be Improving Vocational School Student’s Speaking Skill Using Role Play and Video Clips.it can be valuable as the information resource for students, teachers, and the researcher.